2011
DOI: 10.1103/physrevlett.107.245002
|View full text |Cite
|
Sign up to set email alerts
|

Zonal Flow Dynamics and Control of Turbulent Transport in Stellarators

Abstract: The relation between magnetic geometry and the level of ion-temperature-gradient (ITG) driven turbulence in stellarators is explored through gyrokinetic theory and direct linear and nonlinear simulations. It is found that the ITG radial heat flux is sensitive to details of the magnetic configuration that can be understood in terms of the linear behavior of zonal flows. The results throw light on the question of how the optimization of neoclassical confinement is related to the reduction of turbulence.Understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 17 publications
(30 reference statements)
3
51
3
Order By: Relevance
“…[8] and [13]). The zonal flow oscillations have been observed numerically both in global particle-in-cell (PIC) simulations using the EUTERPE code [13,14] and in flux-tube Eulerian simulations using the GENE code [13,15]. They appear to be more pronounced in optimised configuration such as the Wendelstein 7-X (W7-X) [16] whereas their damping is rather strong in a more "classical" heliotron (such as the LHD device).…”
Section: Introductionmentioning
confidence: 99%
“…[8] and [13]). The zonal flow oscillations have been observed numerically both in global particle-in-cell (PIC) simulations using the EUTERPE code [13,14] and in flux-tube Eulerian simulations using the GENE code [13,15]. They appear to be more pronounced in optimised configuration such as the Wendelstein 7-X (W7-X) [16] whereas their damping is rather strong in a more "classical" heliotron (such as the LHD device).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmas 19, 042504 (2012) geometry on zonal flows and turbulence in helical systems. [24][25][26][27] Figure 5(a) shows the power spectra of the turbulent potential fluctuations in the k y space normalized by gyro-Bohm unit T i q ti =eR 0 , which are obtained by integrating the squared potential fluctuations over the k x space P k x hje/ k x ;k y R 0 =T i q ti j 2 i=Dk y , and taking the time averages in the saturated phases for three simulation runs at each radial position. In the plots, we also show the simulation result obtained by using the vacuum (or zero beta) magnetic field configuration at q ¼ 0:65, where the same simulation parameters of the experiment #88343 at q ¼ 0:65 are used except for the field configuration and the values of minimum wavenumbers ðDk x q ti ; Dk y q ti Þ ¼ ð0:126; 0:036Þ.…”
Section: -3 Nunami Et Almentioning
confidence: 99%
“…Due to the twodimensional nature of plasma turbulence in the plane perpendicular to the magnetic field of toroidally confined plasmas, the energetics obey an inverse cascade [2]. Consequently, the ZFs are supposed to gain energy from small-scale drift-wave turbulence by a self-organizing process which was described theoretically [3], observed in nonlinear turbulence simulations [4,5,6], and investigated experimentally in detail [7,8,9,10,11]. It was shown that the flux surface average of the radial derivative of the Reynolds stress ṽ rṽθ is the driving term for ZFs, and that the energy is transferred non-locally in k-space, i.e.…”
mentioning
confidence: 99%